2015
DOI: 10.1073/pnas.1422203112
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of DNA overwinding by reverse gyrase

Abstract: Reverse gyrase, found in hyperthermophiles, is the only enzyme known to overwind (introduce positive supercoils into) DNA. The ATP-dependent activity, detected at >70°C, has so far been studied solely by gel electrophoresis; thus, the reaction dynamics remain obscure. Here, we image the overwinding reaction at 71°C under a microscope, using DNA containing consecutive 30 mismatched base pairs that serve as a well-defined substrate site. A single reverse gyrase molecule processively winds the DNA for >100 turns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
4
20
1
Order By: Relevance
“…Some Topo IIA (Topo IV, gyrase, and human Topo IIα) are affected by the chirality of DNA Wr supercoiling (Drlica 1992). Reverse gyrase is a unique Type IA topoisomerase combined with a helicase that introduces positive supercoils in an ATP-dependent manner (Ogawa et al 2015;Schoeffler and Berger 2008). The mechanism of positive supercoiling has not been completely established, but it is known that the rate and extent of positive supercoiling are limited by the positive torque on the DNA (Ogawa et al 2015(Ogawa et al , 2016.…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some Topo IIA (Topo IV, gyrase, and human Topo IIα) are affected by the chirality of DNA Wr supercoiling (Drlica 1992). Reverse gyrase is a unique Type IA topoisomerase combined with a helicase that introduces positive supercoils in an ATP-dependent manner (Ogawa et al 2015;Schoeffler and Berger 2008). The mechanism of positive supercoiling has not been completely established, but it is known that the rate and extent of positive supercoiling are limited by the positive torque on the DNA (Ogawa et al 2015(Ogawa et al , 2016.…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
“…Reverse gyrase is a unique Type IA topoisomerase combined with a helicase that introduces positive supercoils in an ATP-dependent manner (Ogawa et al 2015;Schoeffler and Berger 2008). The mechanism of positive supercoiling has not been completely established, but it is known that the rate and extent of positive supercoiling are limited by the positive torque on the DNA (Ogawa et al 2015(Ogawa et al , 2016. In contrast to Topo IB, the catalytic activities of both Topo IA and IIA decrease with increasing positive torsion, suggesting that the rate-limiting step depends on the torque on the DNA (Charvin et al 2005a;Dekker et al 2002;Ogawa et al 2016;Seol et al 2013a).…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
“…By working in opposition these two topoisomerases establish a dynamic supercoiling equilibrium that maintains the DNA at a specific level of negative supercoiling (Drlica 1992). Reverse gyrase is a unique type IA topoisomerase combined with a helicase that introduces positive supercoils in an ATP dependent manner (Ogawa et al 2015; Schoeffler and Berger 2008). Whereas the mechanism of positive supercoiling has not been completely established, the rate and extent of positive supercoiling are limited by the positive torque on the DNA (Ogawa et al 2016; Ogawa et al 2015).…”
Section: Dna Twist (Torsion) Dependent Protein Activitymentioning
confidence: 99%
“…In a previous study [25], we observed the overwinding reaction under a microscope by tethering a magnetic bead to a coverslip surface with a linear DNA and pulling the bead upward with a magnet. In the presence of reverse gyrase and ATP, the bead rotated continuously to relax the DNA wound by reverse gyrase.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of the previous work [25] was that the tension and torsional stress in the DNA could not be independently controlled only by magnetic tweezers, and thus it is still unclear how the torsional stress affects the overwinding rate. In this work we have overcome such limitation by varying the number of working reverse gyrase molecules or the medium viscosity under a constant tension.…”
Section: Introductionmentioning
confidence: 99%